Inpatient Massage Therapy Versus Music Therapy Versus Usual Care: A Mixed-methods Feasibility Randomized Controlled Trial - Eric J Roseen DC; Oscar Cornelio-Flores MD; Chelsey Lemaster MS, MPH; Maria Hernandez MD, MT-BC; Calvin Fong MD; Kirsten Resnick MS; Jon Wardle ND, PhD; Suzanne Hanser EdD; Robert Saper MD, MPH (SAGE Publishing, 2017)
Background Little is known about the feasibility of providing massage or music therapy to medical inpatients at urban safety-net hospitals or the impact these treatments may have on patient experience. Objective To determine the feasibility of providing massage and music therapy to medical inpatients and to assess the impact of these interventions on patient experience. Design Single-center 3-arm feasibility randomized controlled trial. Setting Urban academic safety-net hospital. Patients Adult inpatients on the Family Medicine ward. Interventions Massage therapy consisted of a standardized protocol adapted from a previous perioperative study. Music therapy involved a preference assessment, personalized compact disc, music-facilitated coping, singing/playing music, and/or songwriting. Credentialed therapists provided the interventions. Measurements Patient experience was measured with the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) within 7 days of discharge. We compared the proportion of patients in each study arm reporting "top box" scores for the following a priori HCAHPS domains: pain management, recommendation of hospital, and overall hospital rating. Responses to additional open-ended postdischarge questions were transcribed, coded independently, and analyzed for common themes. Results From July to December 2014, 90 medical inpatients were enrolled; postdischarge data were collected on 68 (76%) medical inpatients. Participants were 70% females, 43% non-Hispanic black, and 23% Hispanic. No differences between groups were observed on HCAHPS. The qualitative analysis found that massage and music therapy were associated with improved overall hospital experience, pain management, and connectedness to the massage or music therapist. Conclusions Providing music and massage therapy in an urban safety-net inpatient setting was feasible. There was no quantitative impact on HCAHPS. Qualitative findings suggest benefits related to an improved hospital experience, pain management, and connectedness to the massage or music therapist.